Analisis Laik Fungsi Jl. K.H. Hasyim Ashari Sampai Jl. Gatot Subroto - Muhammad Rafi Mu’arif (Pusat riset dan Inovasi Nasional, 2023)
Jalan K.H. Hasyim Ashari to Jl. Gatot Subroto is a transportation that plays an important role in daily activities, where Jl. Gatot Subroto is the furniture industry route and the road connects to the Bangil-Rembang toll road. On the K.H. Hasyim Ashari road, the road is connected to the Pantura road so that several points of the road are damaged and bumpy which are caused by heavy vehicles. On the section Jl. K.H. Hasyim Ashari to Jl. Gatot Subroto The method for this study uses a qualitative method in determining road eligibility, in collecting data by field observations, visual analysis and literature study based on Minister of Public Works Regulation Number 11/PRT/M/2010. So that in the condition of the Jl. K.H. Hasyim Ashari Until Jl. Gatot Subroto, in accordance with Regulation of the Minister of Public Works No.11/PRT/M/2010, is a road segment with a conditional function-worthy category (LS) so that several components need to be handled as can be seen in tables 4.169 to 4.175